Climatic influence of forests - Pope, Willis Thomas (My University, 1898)
Introduction: In the rudest stages of life, man depends upon spontaneous animal and vegetable growth for food and clothing, and his consumption of such products consequently diminishes the numerical abundance of the species which serve his use. At more advanced periods, he protects and propagates certain vegetables, plants and animals, and at the same time, wars upon rivals which prey upon these objects of his care or obstruct the increase of their numbers. The action of man upon the organic world tends to subvert the original balance of its species, and while it reduces the number of some of them, or even exterminates them altogether, it multiplies other forms of animal and vegetable life. The extension of the various industries has enlarged the sphere of man’s domain by encroachment upon the forests which once covered the greater part of our earth’s surface, otherwise adopted to his occupation.
Citation: Pope, Willis Thomas. Climatic influence of forests. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Animal; Vegetable; Climate; Forests; Theses; Manuscripts (documents)